Study on Autogenous Heat Technology of Offshore Oilfield: Experiment Research, Process Design, and Application - Yanping Sun; Chengsheng Wang; Jun Sun; Shuliang Ren; Hua Peng; Yueyue Fang; Fangxue Xu (Geofluids)
Conventional heavy oil has abundant reserves and low recovery efficiency in offshore oilfields. Autogenous heat technology uses 2-3 kinds of inorganic salt solution to produce inert gas and release a lot of heat under the action of a catalyst. It is applied to improve heavy oil recovery of the offshore oilfield. This paper applies experimental schemes such as viscosity reduction rate evaluation, heat conditions, gas production conditions, reaction rate control, and effect of environmental factors. This paper evaluates the performance of the autogenous heat system, optimizes the process parameters, and designs the process scheme and construction scheme according to the oil well production. This paper researches an autogenous heat system with nontoxic and high heat production and optimizes the catalyst type, concentration, and time to reach exothermic peak. When the concentration of the thermogenic agent is 1.5 mol/L in the autogenous heat system, the range of temperature rise is 67°C, which achieves the target requirement of more than 50°C. Field application shows that the autogenous heat system can effectively reduce the viscosity of heavy oil, dissolve solid paraffin, clean organic scale, improve reservoir permeability, and increase heavy oil production. This paper applies autogenous heat technology to improving the efficiency of heavy oil recovery of the offshore oilfield. Research conclusions show that the autogenous heat system can effectively reduce the viscosity of heavy oil, improve reservoir permeability, and increase heavy oil production.